Sonographic Analysis of CureJet Injection Depth Consistency After Abdominal Stretch Mark Treatment Using Hyperdiluted Calcium Hydroxylapatite - JongSeo Kim, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. This study investigates the effectiveness and consistency of needle-free jet injectors in administering injections at uniform depths, particularly for the treatment of stretch marks. Ensuring consistent injection depth is crucial for achieving optimal therapeutic outcomes, especially when dealing with challenging skin conditions like stretch marks. Methods:. A retrospective study was conducted involving 25 patients treated for abdominal stretch marks using a needle-free injector (CureJet). For each patient, 10 injection sites were assessed via ultrasound, and the depth of the injections was measured. The mean injection depths and standard deviations were calculated for each patient to assess the consistency of injections. The injected substance was diluted calcium hydroxylapatite, a well-known biostimulatory agent used for skin rejuvenation. Injections were repeated over multiple sessions with consistent parameters to evaluate the reproducibility of the technique. Results:. The mean injection depth across patients was 0.5126 mm, with considerable variability observed between patients. The standard deviation ranged from 0.0326 to 0.2132 mm, indicating significant differences in the consistency of injection depths. The statistical analysis demonstrated that the needle-free injector achieved variable depths, with some injections penetrating deeper than intended, whereas others remained superficial. Conclusions:. While needle-free injectors like CureJet provide a promising alternative to conventional needles, achieving consistent injection depths remains a challenge. This study highlights the need for further refinement in injector technology and technique to improve uniformity in treatment depth, particularly for applications like scar treatment and stretch mark reduction. Enhancing precision in such devices could lead to better patient outcomes and increased safety in aesthetic treatments.